Roswell Randall Hoes papers - Hoes, Roswell Randall, 1850-1921.
Correspondence, notebooks, ship records, printed matter, and other papers relating chiefly to the Spanish-American War and its aftermath. Subjects include Hoes's Spanish-American War collection, Leonard Wood's service as military governor of Cuba, congressional inquiry into Wood's conduct during the American occupation, U.S. Navy Chaplain Corps, United States Naval Academy, USS Kearsarge (Battleship), USS Olympia (Cruiser), and other naval affairs. Correspondents include Marcus Alonzo Hanna, Estes G. Rathbone, Theodore Roosevelt, Elihu Root, Henry Moore Teller, and family and military colleagues of Leonard Wood.
Naval officer and chaplain.
Collection material in English and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Rathbone, Estes G. -- 1847-1926 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Teller, Henry Moore, -- 1830-1914 -- Correspondence; Wood, Leonard, -- 1860-1927.; Wood family -- Correspondence; United States. -- Navy. -- Chaplain Corps; Kearsarge (Battleship); Olympia (Cruiser); United States Naval Academy; Spanish-American War, 1898.; Spanish-American War, 1898 -- Cuba; Cuba -- History -- 1899-1906.; Cuba -- Foreign relations -- United States; United States -- Foreign relations -- Cuba; United States -- History, Naval; Chaplains, Military; Naval officers